Cystine Dimethyl Ester Induces Apoptosis Through Regulation of PKC-δ and PKC-ε in Prostate Cancer Cells - Gurbuz, Nilgun; A. Park, Margaret; Dent, Paul; B. Abdel Mageed, Asim; C. Sikka, Suresh; Baykal, Asli (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Protein kinase C-δ (PKC-δ) and PKC-ε are reported to be effective in cancer prevention via S-thiolationmediated mechanisms. This may be through stimulation of the pro-apoptotic, tumor-suppressive isozyme PKC-δ and/or inactivation of the growth stimulatory, oncogenic isozyme PKC-ε. We investigated oxidative regulatory responses of PKC-δ and PKC-ε to cystine dimethyl ester (CDME), a metabolic precursor of cystine, which, by inducing release of cellular cystine stimulates apoptosis in different prostate cancer cells, PC3 and LNCaP, compared to normal RWPE1 cells. Treatment of CDME in doses of 0.5mM and 5mM significantly induces apoptosis due to regulation of concentration-dependent PKC-δ stimulation and PKC-ε reduction in these prostate cancer cells. This apoptotic regulation was confirmed by immunoblot analyses and specific PKC enzyme assays in immunoprecipitated samples. Additionally, inhibition of PKC-δ by small interfering RNA (siRNA) proved that CDMEinduced cell death was dependent on PKC-δ activity in prostate cancer cells. These data demonstrated that CDME induces apoptosis by cysteinylation of both PKC-δ and PKC-ε in tumorigenic prostate epithelial cells compared to control nontumorigenic cells. Cellular cystine may play a critical role in treatment and/or prevention of prostate cancer by regulating PKC activity.
Keywords: CDME